Real-Life State of Anti-Hepatitis B Virus Drug Choice in Child-Bearing Age Male Patients and Effect on Fertility and Fetal Safety - Zhao X. Hu; Yi N. Ye; Wei G. Wu; Xu J. Liang; Qi W. Wu; Ao Zhang; Xing R. Zheng; Zhi L. Gao; Liang Peng; Chan Xie (Canadian Journal of Gastroenterology and Hepatology)
Research on effects of anti-hepatitis B virus (HBV) nucleoside analogs on male fertility and birth defects is limited and safety of nucleoside analogs in pregnancy is still a concern. Chronic hepatitis B (CHB) patients in Guangdong province were surveyed using a structured questionnaire. We collected data including medication type, fertility, and birth defects. Moreover, a survey of the knowledge of antiviral nucleoside analogs safety in fertility of male patients was conducted among physicians nationwide. Semen samples of 30 patients were collected. We screened 1050 HBV-positive male patients. Reasons for not receiving antivirals in 150 patients were “did not meet criteria for antiviral therapy,” fertility, and financial. Furthermore, 900 participants received antivirals (85.71%, 900/1050), including 792 patients with children and 15.15% (120/792) took anti-HBV treatment when preparing for pregnancy. Based on whether they received antiviral therapy during conception or not, we divided patients into two groups. In the child-bearing age group, 88.33% (106/120) of patients received telbivudine (LDT), whereas the other group mainly received entecavir (ETV) (87.20%, 586/672). No significant difference occurred in birth defect incidence rates between both groups. Furthermore, 558 physicians completed questionnaires. Reasons that influenced drug selection were “patient’s condition,” “fertility demand,” “financial condition,” and “compliance.” Telbivudine was the first-choice drug (32.80%, 183/558) while tenofovir (TDF) was the second (2.69%, 15/558). Additionally, 61.47% of physicians considered telbivudine or tenofovir as the first choice for male patients who met antiviral criteria, whereas 19% suggested delayed therapy and follow-up until childbirth. No significant changes occurred in semen volume, concentration, mobility, and percentage before and after administration of anti-HBV nucleoside analogs, which did not affect male fertility and birth defect incidence while the desire for pregnancy influenced drug selection and timing of administration. Further research on the effects of analogs on male fertility and fetal safety is required.